Academic, Personal, and Administrative Support in an Online Learning of State Universities and Colleges in Camarines Sur, Philippines (Journal of Advanced Research in Social Sciences, 2022)
The COVID-19 pandemic has prompted educational institutions, to shift from traditional to online learning platforms which bring new challenges to learners. This study employed descriptive analysis to examine the learning barriers of “first-time online learners” and the extent of academic, administrative and personal learner support of selected state universities and colleges (SUCs) in Camarines Sur, Philippines. There were 285 students and four key informants who participated in the study. Emotional and mental distress, the intermittent internet connection and financial difficulties are the main learning barriers. Students’ emotional and mental distress could be attributed to numerous obstacles that they experience, such as lack of social interaction, inconsiderate and hard-to-reach teachers, family concerns and poor time management. Based on the respondents’ assessment, the support services provided by SUCs are implemented very extensively. However, not all SUCs assess the learner’s willingness and readiness for online learning, provide financial aid, and offer tutorial centers.